Performance evaluation of a full-scale open bed biofilter through on-site measurements and CFD analyses - Celikten, Hakan; Kuzu, S. Levent; Saral, Arslan; Aksel, Murat (ELSEVIER, 2021)
Composting process is applied to stabilize organic solid waste. But this method releases odorous organic compounds as by-product. Several methods are employed to cope with this nuisance problem. In this study, a full-scale biofilter unit was evaluated which is used in the treatment of composting waste gas. The performance of the open bed biofilter was evaluated by measurements volatile organic compounds (VOCs) and total organic carbon (TOC) from the inlet sampling ports and the outlet of the biofilter. Different sampling points were selected at the outlet of the biofilter in order to better represent removal efficiencies (RE) and determine the variability over the biofilter surface. The average TOC removal rate was 67 +/- 11 %. Fifty-six different VOCs were sampled and then quantified by GC-MS. The average inlet concentrations for the target VOCs fed to the biofilter unit in November, January, April, May, and June were 57.9, 11.51, 4.54, 5.09, and 10.26 mg m-3, respectively and the removal efficiencies for these inlet concentrations were 45 %, 62 %, 32 %, 32 %, and 40 %, respectively. The deterioration of the packing material, caused reduced removal efficiencies by the time. The VOC removal rates were lower than TOC removal rates due to the selected VOC species. Further analyses were conducted with computational fluid dynamics (CFD). The effectiveness of the waste gas distribution was evaluated. Flow distribution within the biofilter was not uniform. This was also supported by the measurement results. Regions of the biofilter volume that are close to the inlet pipe had smaller retention times, which resulted in reduced treatment efficiencies. (c) 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: VOC removal; TOC; Open bed biofilter; CFD; Composting; VOLATILE ORGANIC-COMPOUNDS; SOLID-WASTE MANAGEMENT; BIOGENIC EMISSIONS; UV PRETREATMENT; PRESSURE-DROP; GREEN WASTE; AIR STREAM; BIOFILTRATION; BTEX; ODORS; Engineering